The professional profile of UFBA nursing management graduate students - Paiva, Mirian Santos; Coelho, Edméia de Almeida Cardoso; Nascimento, Enilda Rosendo do; Melo, Cristina Maria Meira de; Fernandes, Josicelia Dumêt; Santos, Ninalva de Andrade (Revista da Escola de Enfermagem da USP, 2011)
The objective of the present study was to analyze the professional profile of the nursing graduate students of Federal University of Bahia, more specifically of the nursing management area. This descriptive, exploratory study was performed using documental research. The data was collected from the graduates' curriculum on the Lattes Platform and from the graduate program documents, using a form. The study population consisted of graduates enrolled under the line of research The Organization and Evaluation of Health Care Systems, who developed dissertations/theses addressing Nursing/Health Management. The data were stored using Microsoft Excel, and then transferred to the STATA 9.0 statistical software. Results showed that most graduates are women, originally from the State of Bahia, and had completed the course between 2000 and 2011; faculty of public institutions who continued involved in academic work after completing the course. These results point at the program as an academic environment committed to preparing researchers.